Asuhan Keperawatan Pada Nn. S dengan Post Operasi Hernioraphy : Hernia Inguinalis Lateralis Dextra di Ruang Mawar 2 RSUD dr. Soeselo Kabupaten Tegal - Silvia Desti Arlina; Ahmad Zakiudin; Sukirno Sukirno (LPPM STIKES KESETIAKAWANAN SOSIAL INDONESIA, 2024)
Inguinal hernia is a condition where an organ protrudes into a cavity through a thin or weak part of the wall. The small intestine is usually the organ that enters the cavity, causing the protrusion. In 2018, hernia ranked 8th in Indonesia with a total of 18,145 cases or around 1.05%. The number of hernia cases in Central Java is estimated to be over 500, or approximately 1.01% of cases. If an inguinal hernia is not treated promptly, it will continue to grow and exert significant pressure on the surrounding tissues. A common consequence of untreated hernia is that it will enlarge and interfere with the patient's daily activities. One of the complications of hernia is swelling around the lump. One of the treatments for hernia is surgery. The writer is expected to provide optimal nursing care for patient. S, who has experienced a right lateral inguinal hernia post- operatively following herniorraphy in Mawar 2 ward of dr. Soeselo Regional Hospital, Tegal Regency.